Study of Streptococcus suis invasion and adhesion on U937 cells - Yinsai, Orathai; Thananchai, Hathairat; Duangsonk, Kwanjit (Biomedical Sciences and Clinical Medicine, 2024)
Objective To investigate the ability of 5 S. suis strains in invasion and adhesion to human monocytic cell line (U937) Materials and methods In this study, 5 strains of Streptococcus suis serotype 2 including P1/7, LPH210/53, TSK10.4, and serotype 14 including MNCM07 and TD2.2 isolated from patients, diseased pig and healthy pig were cultured. All strains were used to test their invasive and adherent efficiency on U937 monocytic cells by bacterial invasion and adhesion assay. Results From the study of interaction between 5 strains of S. suis and U937 cells reveals that S. suis had %Invasive bacteria ranging from only 0.002 to 0.270% of total inoculum bacteria and strain LPH210/53 significantly had the highest invasive ability at all MOI tested. For amount of adherent bacteria on U937 cells, all 5 strains of S. suis had %Adherent bacteria ranging from 3-14% of total inoculum bacteria. LPH210/53 and TD2.2 strains could significantly adhere with the higher amount of bacteria than other strains at MOI=10. Moreover, comparison in the same strain of S. suis at different MOI shows that there was no significant difference in amount of adherent bacteria except strains LPH210/53 and TD2.2, in which at MOI=10 could adhere in significantly higher amount than others MOI. Conclusion S. suis LPH210/53 had the highest invasive ability at 0.270% of total inoculum. For ability of U937 cell surface adhesion, LPH210/53 and TD2.2 strains could significantly adhere more than other strains at MOI=10. This study indicates that each strain of S. suis had the ability to adhere differently on this monocytic cell line in spite of serotypes or isolated sources and other associated factors may be involved. Moreover, this study could lead to the more understanding of pathogenesis mechanisms and development of S. suis infection treatment.